Salamanders in Regeneration Research Methods and Protocols - Kumar, Anoop; Simon, András; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This detailed volume focuses on best practices and conditions for maintaining the most commonly used salamander species in the laboratory. Salamanders in Regeneration Research: Methods and Protocols guides readers through experimental manipulations in vivo and in vitro, respectively. With methods on targeting a wide variety of structures, ranging from the limb to the heart and to the brain, and methods for studying genetically modified organisms and tools for mining in the genomic databases. Written in the highly successful Methods in Molecular Biology series format, chapters include introduction to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Authoritative and up-to-date, Salamanders in Regeneration Research: Methods and Protocols provides a comprehensive collection of methods chapters.
Variation in Salamanders: An Essay on Genomes, Development, and Evolution -- Maintaining Eastern Newts (Notophthalmus viridescens) for Regeneration Research -- Housing and Maintenance of Ambystoma mexicanum, the Mexican Axolotl -- Husbandry of Spanish Ribbed Newts (Pleurodeles waltl -- Maintaining Plethodontid Salamanders in the Laboratory for Regeneration Studies -- Newt Lens Transdifferentiation: From Lentectomy to Immuno-FISH -- Studying Newt Brain Regeneration Following Subtype Specific Neuronal Ablation -- The Accessory Limb Model: An Alternative Experimental System of Limb Regeneration -- High-efficiency Electroporation of the Spinal Cord in Larval Axolotl -- Pseudotyped Retroviruses for Infecting Axolotl -- Thyroxine Induced Metamorphosis in the Axolotl (Ambystoma mexicanum) -- Generation of Aneurogenic Larvae by Parabiosis of Salamander Embryos -- In vivo Modulation and Quantification of microRNAs During Axolotl Tail Regeneration -- Derivation and Long-Term Culture of Cells from Newt Adult Limbs and Limb Blastemas -- Culture and Transfection of Axolotl Cells -- Isolation and Culture of Neurospheres from the Adult Newt Brain -- Methods for Axolotl Blood Collection, Intravenous Injection and Efficient Leukocyte Isolation from Peripheral Blood and the Regenerating Limb -- Assessing Cardiomyocyte Proliferative Capacity in the Newt Heart and Primary Culture --  Long Term Organ Cultures of Newt Hearts -- In vitro Preparation of Newt Inner Ear Sensory Epithelia as a Model for Repair and Regeneration -- Transgenesis in Axolotl (Ambystoma mexicanum) -- Generating and Identifying Axolotls with Targeted Mutations using Cas9 RNA‐guided Nuclease -- Gene Manipulation for Regenerative Studies using the Iberian Ribbed Newt, Pleurodeles waltl -- Transcriptomics Using Axolotls -- Sal-Site: Research Resources for The Mexican Axolotl -- Data Mining in Newt-omics, the Repository for Omics Data from the Newt.
Keywords: Cell biology; Cell Biology